A two-layer portfolio model based on machine learning for productivity prediction of garment industry - Zhou, Yiran (Nanyang Technological University, 2023)
Nowadays, garment industry is one of the most important sectors in this globalized industrial world. Being a labor-intensive industry, production heavily depends on workers' productivity in different factory departments. In this way, the common problem in this industry emerges: the actual productivity of employees fluctuates so that sometimes the target production goals can not be met. This gap between target productivity and real productivity usually causes obstacles to the flow of value chain, furthermore leads to economy and reputation loss to the companies. So, this issue is eagerly anticipated to be solved.